2013
DOI: 10.1039/c3cp53108b
|View full text |Cite
|
Sign up to set email alerts
|

Free radical routes for prebiotic formation of DNA nucleobases from formamide

Abstract: Modeling the complicated chemical reactions in the interstellar medium and surface materials of Titan is nontrivial. Since both the atmosphere and the surface are rich in organic molecules, the chemistry may have important implications for the origin of biomolecules. Prebiotic synthesis of DNA nucleobases from simple molecules such as formamide has been known for more than half a century. In this study, new free radical pathways leading to the synthesis of guanine, hypoxanthine, purine, and adenine have been s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
68
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(71 citation statements)
references
References 48 publications
3
68
0
Order By: Relevance
“…However, this spectrum is rich in other dissociation fragments, such as ∙NH and ∙CH. In all the spectra, the most prominent bands belong to CO, CO 2 , HCN and the unstable radical ∙CN 5,7,42,43 . Specifically, the main species and their detected states in the emission spectra are the following: A 2 Π − X 2 Σ + Δv = 2, 3 and rotation vibration bands of the ground electronic state X 2 Σ + Δv = 1 ∙CN; X 3 Σ − rotation−vibration lines of ∙NH; 2 Π of the radical ∙CH (very weak but detectable only in formamide) and stable products such as the v 1 band of HCN and its unstable isomer 13 HNC and a series of the rows of very strong highly excited rotational−vibrational transitions of CO together with strong atomic emission lines C I (e.g., strong line 3 P 0 − 3 D, 2684.51 cm −1 ); H I (very strong infrared α−Brackett series approximately 2469 cm −1 ); O I (e.g., weaker line 5 D 0 − 5 F 2576.14 cm −1 ); N I (e.g., weaker line 2 D 0 − 2 F 3109.35 cm −1 ); and, finally, the infrared electronic transition W 3 Δ u –B 3 Π g of N 2 .
Figure 3Comparison of the discharge plasma emission spectra of NH 3 : CO: H 2 O and various gas and vapour mixtures in nitrogen.
…”
Section: Resultsmentioning
confidence: 99%
“…However, this spectrum is rich in other dissociation fragments, such as ∙NH and ∙CH. In all the spectra, the most prominent bands belong to CO, CO 2 , HCN and the unstable radical ∙CN 5,7,42,43 . Specifically, the main species and their detected states in the emission spectra are the following: A 2 Π − X 2 Σ + Δv = 2, 3 and rotation vibration bands of the ground electronic state X 2 Σ + Δv = 1 ∙CN; X 3 Σ − rotation−vibration lines of ∙NH; 2 Π of the radical ∙CH (very weak but detectable only in formamide) and stable products such as the v 1 band of HCN and its unstable isomer 13 HNC and a series of the rows of very strong highly excited rotational−vibrational transitions of CO together with strong atomic emission lines C I (e.g., strong line 3 P 0 − 3 D, 2684.51 cm −1 ); H I (very strong infrared α−Brackett series approximately 2469 cm −1 ); O I (e.g., weaker line 5 D 0 − 5 F 2576.14 cm −1 ); N I (e.g., weaker line 2 D 0 − 2 F 3109.35 cm −1 ); and, finally, the infrared electronic transition W 3 Δ u –B 3 Π g of N 2 .
Figure 3Comparison of the discharge plasma emission spectra of NH 3 : CO: H 2 O and various gas and vapour mixtures in nitrogen.
…”
Section: Resultsmentioning
confidence: 99%
“…Although the impact energies were most likely not large enough to produce ocean evaporation or globally sterilizing events (16), they could have served as local energy sources for biomolecule synthesis (17)(18)(19)) Therefore, the high-impact activity may not have been harmful for the formation of biomolecules and the first living structures. Conversely, it may have been the source of energy required to initiate chemical reactions, such as the synthesis of biomolecules (20).…”
mentioning
confidence: 99%
“…2, several species that are very similar to the discharge of pure formamide can be observed (19). In all of the spectra, the most prominent bands belong to CO, CO 2 , HCN, and HNC excited to high vibration-rotation levels and the unstable but ubiquitous radical ·CN, which can play an important role in the subsequent plasma synthesis of nucleobases (18)(19)(20). Stable molecules, such as ammonia, carbon monoxide, acetylene, nitrous oxide, and hydrogen cyanide, were identified by high-resolution infrared absorption spectroscopy during subsequent analysis of discharge products concentrated in liquid-nitrogen trap.…”
Section: Resultsmentioning
confidence: 94%
“…Finally, many scientists have claimed that this experiment is not related to early-Earth conditions and does not provide fundamental building blocks (i.e., nucleobases) important for the evolution of early life possibly based on RNA (7)(8)(9)(10)(11)(12)(13). In 2001, Saladino, Di Mauro, and coworkers (14) proposed that the parent molecule for the one-pot synthesis of nucleobases is formamide (15)(16)(17)(18)(19)(20)(21)(22)(23). Their team, together with other authors, demonstrated the formation of (not only) fundamental nucleobases for the origin of RNA in experiments involving the heating of formamide in presence of manifold catalysts (17,(24)(25)(26), upon UV irradiation (27), proton (28) and heavy-particle radiation (29), exposition to shock waves (18), etc.…”
mentioning
confidence: 99%